Gambaran Kejadian Diare Balita di Kabupaten Minahasa Utara tahun 2021-2023 - Julio Martin Pasimanyeku; Jeini Ester Nelwan; Fima Langi (Universitas Sam Ratulangi, 2024)
Diarrhea in underfive children is a disease with a fairly short pathogenesis, but can be fatal if not given good management, especially in pediatric patients. The purpose of this study is to describe the incidence of diarrhea underfive children in North Minahasa in 2021-2023. This is a quantitative research will be carried out in North Minahasa Regency in April-May 2023. The variables studied are the incidence of toddler diarrhea in North Minahasa based on time and place in 2021-2023. This study used secondary data from the North Minahasa District Health Office. The data obtained are then analyzed descriptively. The results showed that the prevalence of underfive children diarrhea in 2021 was 473 cases, of which the most cases were found at the Kauditan Health Center, which was 80 cases and the most occurred in May as many as 231 cases. The prevalence of diarrhea underfive children in 2022 is 474 cases, of which the most cases are found at the Kauditan Health Center, which is 60 cases and the most occur in January, August and November, each with 60 cases. The prevalence of diarrhea underfive children in 2023 (January-February) is 86 cases, of which the most cases are found at the Kolongan Health Center, which is 28 cases, in January 2023 as many as 51 cases. It can be concluded that the most cases of underfive children diarrhea were found in Kolongan and Kauditan Health Centers in January. Therefore, it is necessary to make efforts to prevent toddler diarrhea such as health promotion, risk factor screening and others.